A Mobile Application That Allows People Who Do Not Know Sign Language to Teach Hearing-Impaired People by Using Speech-to-Text Procedures - Emre BIÇEK; M. Nuri ALMALI (International Journal of Applied Methods in Electronics and Computers, 2020)
Hearing-impaired people use sign language to communicate with each other. People who do not know sign language it is difficult to communicate with hearing-impaired people. In this study, this problem is tried to solve with speech-to-text infrastructure. A software project has been developed to enable people who do not know sign language to communicate with the hearing impaired people. The scope of the system which named "Subtitles Course Tracking System (SCTS)" is that with an application running on the Android operating system, user’s speeches are converted into text (Speech-to-Text) and instantly transferred to remote a server. Speech texts which are recorded on the database of the remote server could be followed up in real-time on mobile phones and web pages by the software that has capable of asynchronous data exchange over the Internet (AJAX). Within the scope of this study, a web-based course management system has been developed and all courses in the system made accessible at any time.